2022
DOI: 10.1186/s40364-022-00395-z
|View full text |Cite
|
Sign up to set email alerts
|

High expression of TMEM244 is associated with poor overall survival of patients with T-cell lymphoma

Abstract: T-cell lymphoma (TCL) is an aggressive and genetically heterogeneous malignancy with adverse clinical outcomes; thus, it is worth exploring biomarkers for risk stratification. Previous studies have demonstrated that transmembrane protein 244 gene (TMEM244) is ectopically expressed in Sézary syndrome (SS). In this study, the expression level of TMEM244 and its prognostic value for TCL patients was explored by analyzing RNA-seq data of two large datasets (GSE132550 and GSE113113) containing 129 TCL patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The endpoint of this study was OS, and the OS was defined as the time from the date of diagnosis to the date of death or last follow‐up time. 8 , 16 , 22 , 23 , 24 , 25 Whole‐exome sequencing data from 121 T‐ALL patients in the PRJCA002270 dataset, including 96 children, 22 adults, and 3 cases of unknown age, were downloaded from the BioProject database ( https://ngdc.cncb.ac.cn/bioproject/browse/PRJCA002270 ). 26 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The endpoint of this study was OS, and the OS was defined as the time from the date of diagnosis to the date of death or last follow‐up time. 8 , 16 , 22 , 23 , 24 , 25 Whole‐exome sequencing data from 121 T‐ALL patients in the PRJCA002270 dataset, including 96 children, 22 adults, and 3 cases of unknown age, were downloaded from the BioProject database ( https://ngdc.cncb.ac.cn/bioproject/browse/PRJCA002270 ). 26 …”
Section: Methodsmentioning
confidence: 99%
“… 9 , 10 , 11 , 12 Moreover, genetic alterations exert an important role in prognostic stratification in precision therapy. 13 , 14 , 15 , 16 , 17 Although multiple studies have been conducted to explore the role of genetic alterations combined with minimal residual disease (MRD) in risk stratification for T‐ALL, high heterogeneity has led to difficulty in accurately stratifying all patients. 14 , 18 Therefore, further exploration of novel biomarkers to improve risk stratification for T‐ALL patients is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also revealed that higher expression of TMEM244 was observed either in CD4+ or in CD8+ subsets of memory cells (CD4RO+), which is in line with the immunophenotype of Sézary cells 49 . Furthermore, collaborating with us Chinese group showed that high expression of TMEM244 is associated with poor overall survival of patients with different forms of T-cell lymphoma, including CTCL 50 . Mechanistically, we showed that TMEM244 expression in SS cells is driven by specific hypomethylation of its promoter 48 .…”
Section: Transmembrane Protein Gene 244 (Tmem244)mentioning
confidence: 98%
“…Izykowska et al, were the first to pay attention to the TMEM244 gene, as it was identified among four other genes ( EHD1 , MTMR2 , RNF123 , and TOX ) to be involved in the rearrangements affecting gene expression in Sézary syndrome (SS) patients compared to controls [ 8 ]. Further studies showed that TMEM244 is expressed in T-cell lymphomas as a result of specific hypomethylation of its promoter, and this expression is associated with poor overall survival in T-cell lymphoma patients [ 9 , 10 ]. A significantly higher expression of TMEM244 was identified in Sézary syndrome patients, not only compared to healthy individuals but also to SS clinical mimickers, such as mycosis fungoides and erythrodermic manifestations of non-malignant diseases, therefore indicating its diagnostic potential.…”
Section: Introductionmentioning
confidence: 99%